Sinergisme Lembaga dalam Pengembangan Desa Wisata Lerep - Zahirah, Putri Yasmin Fathina; Prayoga, Kadhung; Prasetyo, Agus Subhan (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
Tourism villages can develop if the community supports them. To accomplish a goal, a community that is part of the institution must be able to perform its duties and functions as a unitary institution. The institutions have to communicate with one another and work together to develop Lerep Tourism Village. This research will outline the roles of each institution and examine this synergism. Based on the institutions participating in the management of the Lerep Tourism Village, the location was chosen using a purposive sampling strategy. This is a qualitative approach with case study research. Purposive sampling was used to select 26 informants to interview, covering head of village and hamlets, leaders and members of institutions, representative of communities from 4 hamlets. In-depth interviews, observation, and documentation were utilized to obtain the data, and evaluated using Miles Huberman’s flow model. The data’s veracity was examined using source triangulation and technique triangulation. The results show that each institution namely Government Institution, Economic Institution, Art and Cultural Institution, Agricultural Institution, and Environmental Institution plays different roles. There are varieties of purposes in institutional synergy. However, institutions have implemented elements of effective communication and coordination. Such synergies lead to the establishment of new tourist attractions and facilities, increase in the number and satisfaction of visitors, job opening and increase in community income, moreover receiving recognition and passing the certification process. There needs to be discussions and follow-up process regarding improving the internal conditions of institutions and communities between hamlets.